2018
DOI: 10.1177/0046958018754739
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Applying Quality Management Practices on Patient Centeredness in Jordanian Public Hospitals: Results of Predictive Modeling

Abstract: Targeting the patient’s needs and preferences has become an important contributor for improving care delivery, enhancing patient satisfaction, and achieving better clinical outcomes. This study aimed to examine the impact of applying quality management practices on patient centeredness within the context of health care accreditation and to explore the differences in the views of various health care workers regarding the attributes affecting patient-centered care. Our study followed a cross-sectional survey des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 50 publications
(86 reference statements)
0
18
0
1
Order By: Relevance
“…The concept of a common standardized international approach to classify/describe rehabilitation services of mistakes and defects and increases the safety of a service. Nowadays it is a mandatory factor in health service delivery in many countries (25)(26)(27). c) Modes of referral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of a common standardized international approach to classify/describe rehabilitation services of mistakes and defects and increases the safety of a service. Nowadays it is a mandatory factor in health service delivery in many countries (25)(26)(27). c) Modes of referral.…”
Section: Discussionmentioning
confidence: 99%
“…b) Quality assurance and management. These are regarded as important factors in a service organization (25,26). Quality assurance and management includes risk management and is connected with quality of structures and processes.…”
Section: Changes In Dimensions Categories and Subcategoriesmentioning
confidence: 99%
“…Furthermore, a study conducted in India among doctors, hospital directors and insurance representatives has shown that respondents had given a high degree of support to the accreditation process [15]. In addition, it is easier for accredited hospitals to better defi ne the role of their institution and the planning of services, which can consequently enable the management to organize health services more adequately [16,17].…”
Section: Questionsmentioning
confidence: 99%
“…In recent years, issues regarding the quality of healthcare have increased considerably in many low-and middle-income countries, including Taiwan. Evidence has shown that all processes and activities necessary for delivering healthcare service need to be controlled using a quality management system [2].…”
Section: Introductionmentioning
confidence: 99%